1998
DOI: 10.1080/00914039808041034
|View full text |Cite
|
Sign up to set email alerts
|

The Fatigue and Hysteresis Behaviour of Filled Epoxidized Natural Rubber Compounds

Abstract: The paper reports on the fatigue behaviour of white rice husk ash (WRHA), silica and carbon black-filled ENR 50 vulcanizates. The properties investigated include the stressstrain behaviour, effect of coupling agent and hysteresis. Carbon black filled vulcanizates showed the highest stress-strain behaviour followed by silica and WRHA. This observation was supported by the plot of accumulated strain energy versus extension ratio. Carbon black showed the highest value followed by silica and WRHA. The incorporatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Interestingly, Fig. The current data is in-line with the trend of the major effects of dynamic vulcanization on the vulcanizate structure, as mentioned by several workers [5,6,13] . One can observe that irrespective of sulfur loading, the fatigue life of PVC=NBR TPEs samples fades as the extension ratio increases.…”
Section: Effect Of Sulfur Concentration On Fatigue Behaviorsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, Fig. The current data is in-line with the trend of the major effects of dynamic vulcanization on the vulcanizate structure, as mentioned by several workers [5,6,13] . One can observe that irrespective of sulfur loading, the fatigue life of PVC=NBR TPEs samples fades as the extension ratio increases.…”
Section: Effect Of Sulfur Concentration On Fatigue Behaviorsupporting
confidence: 91%
“…Furthermore, dynamic vulcanization plays a significant role in TPE technology where it produces thermoplastic vulcanizates with a unique combination of properties. In another related study, Ismail et al [6] reported on the fatigue behavior of filled ENR compounds, as well as their hysteresis. Fatigue is one of the most important long-term test methods and has been used extensively for various rubbers [2][3][4] .…”
Section: Introductionmentioning
confidence: 97%
“…But in case of compression of a viscoelastic material the exact nature of the curve is not known. Hence, the strain energy in case of rubber material is calculated using the Simpson's composite rule or by Trapizoidal rule [7]. The outline of such rule is given in subsection 2.1.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Keeping that perspective in mind researchers in different parts of the globe aim at developing different grades of rubber by reinforcing with organophilic clay, carbon nanofibres, carbon nanotubes, fly ash and so on. Addition of white rice husk ash (WRHA), silica, carbon black in different quantities are also some examples in this regime of reinforcement for the production of differ ent vulcanizates [6,7].…”
Section: Introductionmentioning
confidence: 99%